F. M. DOSTOEVSKY REMEMBRANCE DAYS IN ROSTOV-ON-DON (November11-13, 2013) (Proceedings of Southern Federal University. Philology, 2014)
Cherjukina G.L.Keywords: festival, Dostoevsky F. M., scholarship, artistic activity, conference. The author describes in detail the entire program of the festival devoted to Dostoevsky F.M. memory day, which was held in November, 2013 in Rostov-on-Don. The festival program included a variety of artistic and scientific activities: round tables, conferences, concert, staged fragments of one of Dostoevsky’s F. M. works. The festival aroused the interest of the public and a wide resonance in the media.